2019
DOI: 10.1049/hve.2019.0067
|View full text |Cite
|
Sign up to set email alerts
|

Method of inter‐turn fault detection for next‐generation smart transformers based on deep learning algorithm

Abstract: In this study, an inter-turn fault diagnosis method is proposed based on deep learning algorithm. 12-channel data is obtained in MATLAB/Simulink as the time-domain monitoring signals and labelled with 16 different fault tags, including both primary and secondary voltage and current waveforms. An auto-encoder is presented to classify the fault type of the abundant and comprehensive fault waveforms. The overall waveforms compose a two-dimension data matrix and the auto-encoder is trained to extract the features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Therefore, the more concentrated the volume fraction of the gas is distributed, the more representative it is of that fault type, that is the greater the weight of the gas. In summary, the definition of g here is opposite to that of the entropy value method, and therefore the inverse is taken here, as shown in Equation (18). The weighted vector P (F) of fault F is defined as Equation ( 20):…”
Section: Obtaining Data Weights By Improved Information Entropy Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the more concentrated the volume fraction of the gas is distributed, the more representative it is of that fault type, that is the greater the weight of the gas. In summary, the definition of g here is opposite to that of the entropy value method, and therefore the inverse is taken here, as shown in Equation (18). The weighted vector P (F) of fault F is defined as Equation ( 20):…”
Section: Obtaining Data Weights By Improved Information Entropy Methodsmentioning
confidence: 99%
“…In addition, machine learning methods have been applied to fault diagnosis and achieved good results. For example, neural networks [10,11], fuzzy set theory [12], Bayesian networks [13], set pair theory [14], support vector machines [15,16], Parzen window [17] and other methods [18].…”
Section: Introductionmentioning
confidence: 99%
“…An, Liang et al [29] has proposed a modified hidden Markov model (HMM) fault detection method, which can suppress random and unknown interference and solve the diagnosis problem of RV reducer with complex fault. Duan, Hu et al [30], in order to improve the accuracy and robustness of transformer fault diagnosis, a three-phase transformer turn-turn fault diagnosis method based on deep learning algorithm was proposed. Experimental results showed that the method improved the accuracy of fault classification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intelligent methods are considered as suitable substitutes for improving the performance compared with rule-based DGA methods, such as artificial neural networks (ANNs) [12][13][14], support vector machines (SVMs) [15,16], and relevance vector machines (RVMs) [17]. With similar characteristics in terms of input, intelligent methods can achieve higher diagnostic accuracy than rule-based methods in certain databases [12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%